2018
DOI: 10.1002/evl3.65
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing parasite fitness reveals the basis of specialization in a two-host, two-parasite system

Abstract: The ecological specialization of parasites–whether they can obtain high fitness on very few or very many different host species–is a determining feature of their ecology. In order to properly assess specialization, it is imperative to measure parasite fitness across host species; to understand its origins, fitness must be decomposed into the underlying traits. Despite the omnipresence of parasites with multiple hosts, very few studies assess and decompose their specialization in this way. To bridge this gap, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 77 publications
5
42
0
Order By: Relevance
“…Partitioning the infection process into different components holds the key to resolving the genetic architecture of the entire defence cascade and consolidate our understanding for how different defence components evolve (see also Davis, Meconcelli, Radek, & McMahon, ; Duneau et al, ; Lievens et al, ). In this study, we dissect the genetic architecture of a stepwise infection process using a bacterial pathogen of the water‐flea Daphnia magna ; one of the few model systems with enough knowledge and experimental tools available to do so.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Partitioning the infection process into different components holds the key to resolving the genetic architecture of the entire defence cascade and consolidate our understanding for how different defence components evolve (see also Davis, Meconcelli, Radek, & McMahon, ; Duneau et al, ; Lievens et al, ). In this study, we dissect the genetic architecture of a stepwise infection process using a bacterial pathogen of the water‐flea Daphnia magna ; one of the few model systems with enough knowledge and experimental tools available to do so.…”
Section: Introductionmentioning
confidence: 99%
“…Beginning with the initial contact between a host and pathogen, and ending with the transmission of the pathogen to a new host, are multiple mechanisms that interact to determine a host's susceptibility to infection (i.e., defence portfolios: van Baalen, ; Schmid‐Hempel & Ebert, ; Hall et al, ; Lievens, Perreau, Agnew, Michalakis, & Lenormand, ). A simplified genetic basis is often predicted for steps that occur early in the infection process, whereby having a resistance allele may completely block infection, commonly referred to as “qualitative resistance.” This response is typical of the all‐or‐nothing interaction between many plant species and various pathogens and is often linked to processes involved in the recognition of a pathogen‐produced elicitor (Corwin & Kliebenstein, ; Flor, ; Frank, ; Thompson & Burdon, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two parasites are ecologically 74 similar, can complete their life cycles on both hosts, and commonly infect both hosts in the field (Rode 75 et al 2013b). Nonetheless, they each show a degree of specialization in the lab: A. rigaudi has much 76 higher fitness in A. parthenogenetica, while E. artemiae's fitness is much higher in A. franciscana 77 (Lievens et al 2018). Furthermore, we have shown that A. franciscana is a sink host for A. rigaudi in the 78 field, even though prevalences in this host can reach 100%, and that the same may be true for A.…”
Section: Introduction 28mentioning
confidence: 99%
“…The first, A. parthenogenetica, is an asexual clade native to the area; the second, A. franciscana, is a 92 sexual species that was introduced from North America in 1970 and has since become highly prevalent 93 (Amat et host, but perform much better on one of the two (Lievens et al 2018). A. rigaudi's fitness is considerably 108 higher in A. parthenogenetica, while E. artemiae's is higher in A. franciscana.…”
Section: Introduction 28mentioning
confidence: 99%